Tristan Chord and an Extended Dispute Over a Century - Buranaprapuk, Ampai (Rangsit Music Journal, 2018)
The Tristan chord has been controversially discussed for over a century. There are many analyses that interpret the chord very differently, ranging from functional to totally nonfunctional. This article surveys literature on the chord and presents possible analyses of it, while seeing it in the milieu of other compositions of the nineteenth century. The relation of the Tristan chord to its context is not more complex than that of other works of the nineteenth century. This chord is an example of extremity of chromaticism which is, however, a common phenomenon of the Romantic period.